Kant or not Kant? Arguing on Kant’s Ultimate Political Design for Global Governance and Cosmopolitanism. An Exchange between Claudio Corradetti and Allen Wood - Corradetti, Claudio; Wood, Allen (Con-Textos Kantianos. International Journal of Philosophy, 2021)
In the following reflection Claudio Corradetti and Allen Wood engage in a controversy concerning the possibilities and the limits of textual interpretation. Should an interpreter still be authorized to call an author’s interpretation the logical stretch of text beyond its black printed letters? The authors offer two different standpoints on what can still be defined as textual interpretation. Whereas for Allen Wood a clear-cut separation must be kept between what a text shows and what an interpreter argues starting from the text, for Claudio Corradetti such distinction remains internal to textual exegesis in so far as the interpreter’s conclusions follow a logical pattern of justification starting from evidential hints.